2016
DOI: 10.1093/ee/nvw033
|View full text |Cite
|
Sign up to set email alerts
|

Host Plant Associations ofAnagrusspp. (Hymenoptera: Mymaridae) andErythroneura elegantula(Hemiptera: Cicadellidae) in Northern California

Abstract: Anagrus erythroneurae S. Trjapitzin & Chiappini and Anagrus daanei Triapitsyn are the key parasitoids of the western grape leafhopper (Erythroneura elegantula Osborn) in northern California vineyards. Erythroneura elegantula overwinters as an adult in reproductive diapause. To successfully overwinter, Anagrus spp. must locate an alternate leafhopper host that overwinters in an egg stage that they can parasitize. These alternate leafhopper hosts are thought to be primarily located in the natural habitats surrou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 58 publications
1
3
0
Order By: Relevance
“…on the perennial Baccharis pilularis, which produces abundant nectar. We agree with Wilson et al (2016) that the impact of alternative vegetation on Anagrus spp. will depend on the type and frequency of favored Anagrus spp.…”
Section: Figure 9 Regression Of Log10supporting
confidence: 90%
See 1 more Smart Citation
“…on the perennial Baccharis pilularis, which produces abundant nectar. We agree with Wilson et al (2016) that the impact of alternative vegetation on Anagrus spp. will depend on the type and frequency of favored Anagrus spp.…”
Section: Figure 9 Regression Of Log10supporting
confidence: 90%
“…density, and we found similar results with a cover crop of alyssum (Lobularia maritima) (Costello, Thrupp & McGourty, unpublished data). Wilson et al (2016) found high winter and spring abundance of Anagrus spp. on the perennial Baccharis pilularis, which produces abundant nectar.…”
Section: Figure 9 Regression Of Log10mentioning
confidence: 90%
“…Moreover, while some adult parasitoids are dependent on nectar and/or pollen for food (Heimpel & Jervis, ), plant species can vary widely in their ability to provide these resources (Wäckers, ). A final point is that the current study was conducted in the more arid San Joaquin Valley, where suitable overwintering habitats and hosts are lacking compared with vineyards studied in northern California (Wilson, Miles, Daane, & Altieri, , ) and New York (English‐Loeb et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…The high parasitoid abundance on rosemary (ORG) hedgerows can be attributed to Anagrus spp. (Mymaridae), an egg parasitoid of the Ligurian leafhopper Eupteryx decemnotata Rey (Hemiptera: Cicadellidae) [62]. This typhlocybid leafhopper was recorded in high numbers on rosemary and sage hedgerows; however, symptoms of infestation (yellowing) were observed only on rosemary leaves.…”
Section: Discussionmentioning
confidence: 99%